Isobaric tags for relative and absolute quantification‐based proteomic analysis that reveals the roles of progesterone receptor, inflammation, and fibrosis for slow‐transit constipation. Issue 2 (26th January 2018) - Li, Yuwei; Yu, Yongjun; Li, Shuyuan; Zhang, Mingqing; Zhang, Zhao; Zhang, Xipeng; Shi, Yang; Zhang, Shiwu
Abstract: Background and Aim: Progesterone receptor, inflammation, neurotransmitter expression, and fibrosis are involved in slow‐transit constipation. The aim of the present study was to examine whether patients with slow‐transit constipation have an overexpression of progesterone receptor and serotonin, which may impair the fibrosis of muscularis propria in colorectal wall. Methods: High‐resolution colon manometry was used to record the colorectal peristaltic contractions of the proximal ascending and sigmoid colon in patients. Protein samples prepared from frozen sigmoid colon tissue and the proximal margin of the ascending colon of four female patients were compared using isobaric tags for relative and absolute quantification labeling technique coupled to 2D liquid chromatography–tandem mass spectrometry analysis. Immunohistochemical staining of progesterone receptor, serotonin, and fibronectin was performed in paraffin‐embedded sigmoid colon tissues and the proximal margin of the ascending colon or ileum from 43 patients with slow‐transit constipation. Results: Among these differentially regulated proteins based on isobaric tags for relative and absolute quantification and liquid chromatography–tandem mass spectrometry analysis, 56 proteins involved in the response to progesterone, inflammation, matrix remodeling, fibrosis, and muscle metabolism. Immunohistochemical staining confirmed that there was significantly higher expression of progesterone receptor ( t = 19.19, P = 0.000) and serotonin ( t = 13.52, P = 0.004) in sigmoid colon than in the proximal margin of the ascending colon and ileum. Progesterone receptor and fibronectin expression in the outer layer of muscularis propria were higher than in the middle layer. Conclusions: These results demonstrate that progesterone receptor, along with inflammation and fibrosis, may take part in slow‐transit constipation development.